The Paradigm of Conflict Resolution Educational Model in Building Peace Life Competency Based on Sabilulungan Local Wisdom in Primary Education Students - Tuti Istianti; Enok Maryani; Bunyamin Maftuh; Dinie Anggraeni Dewi (International Conference on Elementary Education, 2023)
The current state of society is in an unstable position or there is national instability and emerging fights among students, gang fights, maltreatment, and bullying cases. School must be a place to instill peaceful character values which become a learning house that is able to provide knowledge, peace and comfort for all school members. The research method in this study used a qualitative descriptive approach with a research site in Cikondang traditional village. Based on the discussion result of the paradigm study of conflict resolution educational model in building peace life competency based on sabilulungan local wisdom in Primary Education, it can be concluded that the information obtained from field studies shows that: a) Schools must be a place to instill peaceful character values which are always faced with unstable social conditions or national instability, for example there are many fights among students, gang fight, maltreatment, and bullying cases, b) Conflict resolution education as the most likely medium for learning conflict resolution as a skill; has a clear and structured method and can be applied in elementary schools, c). Sabilulungan as the tradition of Sundanese people provides local wisdom that has philosophical values that is to build peaceful character, it is considered to be social capital, d) For the benefit of conflict resolution learning by combining contextual problem approach, thinking skill, affective development, student-centered values instilling base.